Productivity and Economics of Machine Transplanted Rice (Oryza sativa L.) as Influenced by Puddling Methods and Spacing - Negalur, R. B.; Halepyati, A. S.; Channabasavanna, A. S. (International Journal of Bio-resource and Stress Management, 2016)
Field experiments were conducted on the effect of different puddling methods and various spacing on growth and yield of machine transplanted rice (Oryza sativa L.) at Agricultural Research Station, Gangavathi, University of Agricultural Sciences, Raichur, Karnataka during kharif, 2012 and 2013 in clay soil under irrigated condition. Pooled mean of two years indicated that among the different puddling methods and spacing. puddling with rotovator fb levelling with spike tooth harrow and spacing of 30×21 cm2 recorded significantly higher dry matter accumulation in leaves (13.44 and 14.43 g plant-1, respectively), stem (26.25 and 29.31 g plant-1, respectively), panicles (37.21 and 41.38 g plant-1, respectively), total dry matter accumulation in plant (73.82 and 85.12 g plant-1, respectively) and leaf area plant-1 (1135 and 1229 cm2, respectively). Similarly, grain yield (4906 and 5192 kg ha-1, respectively), straw yield (6247and 6508 kg ha-1, respectively), gross returns (Rs. 87,733 and 92,779 ha-1, respectively), net returns (Rs. 46,329 and 50,007 ha-1) and benefit cost ratio (2.14 and 2.20) were also recorded with puddling with rotovator fb levelling with spike tooth harrow and 30×21 cm2 spacing. Hence, on the basis of results obtained during both the years, combination of puddling with rotovator fb levelling with spike tooth harrow method of puddling and 30×21 cm2 spacing was found better for transplanting of rice by self-propelled mechanical transplanter for Tungabhadra command area of Karnataka.